Effects of three therapeutic doses of codeine/paracetamol on driving performance, a psychomotor vigilance test, and subjective feelings - Amato, Jean-Noël; Marie, Sullivan; Lelong-Boulouard, Véronique; Paillet-Loilier, Magalie; Berthelon, Catherine; Coquerel, Antoine; Denise, Pierre; Bocca, Marie-Laure (Psychopharmacology, 2013)
Rationale Some recent pharmacoepidemiological studies revealed an elevated risk of driving accidents after opioid analgesics uses. Among analgesics, codeine is often associated with paracetamol in numerous pharmaceutical specialties. Objectives The objective of this study was to evaluate the dose–effect relationship of three usual therapeutic doses of codeine/paracetamol on driving ability, psychomotor performance, subjective alertness, in link with blood concentrations in healthy young volunteers. Methods Driving performance, responses to psychomotor vigilance tests, and scales reflecting alertness were evaluated during the morning after drug intake in a double-blind, randomized, placebo-controlled study. Sixteen healthy volunteers (23.4 ± 2.7 years old, 8 men and 8 women) participated in this balanced, cross-over study. Three doses of codeine/paracetamol (20/400, 40/800, 60/1200 mg) were evaluated against placebo. Two blood samples were collected, 1 and 4 h after drug intake. In serum, codeine and morphine concentrations were determined in serum using high-performance liquid chromatography electrospray ionization-tandem mass spectrometry, and paracetamol concentrations using fluorescence polarization immunoassay. Results Driving and psychomotor performance were not affected by any of the three codeine/paracetamol doses. However, significant, though modest, correlations were observed between the driving parameters and both morphine and codeine blood concentrations. Conclusions This study did not reveal any significant impairment in performance due to the three therapeutic doses used in healthy young volunteers. However, the relationships between drug blood concentration and behavioral measures suggest that an inter-subject variability in blood concentration may influence the power of the observed drug effect.